'Did they think I would understand all that on my own?' A questionnaire study about sexuality with Swedish cancer patients. (25th January 2013) - Rasmusson, E.‐M.; Plantin, L.; Elmerstig, E.
'Did they think I would understand all that on my own?' A questionnaire study about sexuality with Swedish cancer patients This study investigates information about the sexual effects of cancer on patients, irrespective of age or diagnosis, in terms of fertility, sexual desire and sexual function. A quantitative study was conducted and the results are based on responses from 106 questionnaires. The results show that 48% of respondents had not received any information in the areas of inquiry. There was a difference between information wished for and provided, and the largest difference was in the question of whether sexual activity should be avoided. A significantly higher number of men than women received information about effects on fertility and sexual desire. The results also showed that information about sexuality needs to be taken into account to a greater extent than is presently being done.